Triple Bottom Line Insights: Corporate Social Responsibility as a Moderator Between Green Accounting and Firm Value - Edi Triwibowo; Wisnu Setyawan; Dian Sulistyorini Wulandari (Jurnal Riset Akuntansi, 2026)
The increasing emphasis on sustainable business practices has encouraged companies to integrate environmental and social responsibilities into their strategic and financial decision-making processes. This study investigates the influence of Green Accounting on Firm Value and examines the moderating role of Corporate Social Responsibility (CSR) within the Triple Bottom Line framework. A quantitative research design was employed using panel data from 23 energy, mining, and infrastructure companies listed on the Indonesia Stock Exchange during the 2022–2024 period, resulting in 69 firm-year observations. Secondary data were collected from annual reports and sustainability reports and analyzed using descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA). The findings indicate that Green Accounting does not have a significant direct effect on Firm Value, while CSR also shows no significant direct influence. Furthermore, CSR is unable to significantly moderate the relationship between Green Accounting and Firm Value. These results suggest that sustainability initiatives implemented by Indonesian companies have not yet generated measurable short-term financial benefits, although they may contribute to long-term corporate legitimacy, stakeholder trust, and sustainable competitiveness. The study provides practical implications for corporate managers, investors, and policymakers by emphasizing the importance of strengthening sustainability reporting quality and integrating environmental and social strategies into long-term corporate value creation.